The Power and Limits of Reason: Al-Rāzī on the Possibility of General and Particular Metaphysical Knowledge - Eşref Altaş (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This article examines al-Rāzī’s views on the possibility of metaphysical knowledge. Firstly, after outlining his classification of the metaphysical knowable into essence and existence as well as undetailed (ijmālī) and detailed (taf~īlī), the article analyzes al-Rāzī’s acceptance of the possibility of general knowledge of metaphysics under a few headings by delving into some major themes. These include the claims that the category of existence is broader than the world of the sensible, that theoretical reasoning leads to metaphysical knowledge, and lastly that the theoretical evidence provides necessary knowledge about the existence of a creator. Al-Rāzī has also been demonstrated in al-Matālib to have inherited the arguments rejecting metaphysical knowledge, which he had attributed in his earlier works to a group with the name muhandisiyyūn, by restricting them to the issue of God’s essence being knowable. For al-Rāzī, theoretical reasoning could provide knowledge about the existence of a particular metaphysical being but not about its quiddity. The article further underlines the metaphysical and epistemic theses for the position on the unknowability of God’s essence and discusses its semantic interpretation. The debate on the potential of theoretical reason to provide uncertain knowledge of detailed metaphysics in the form of the best possible explanations (the metaphysics of the best explanation, or al-awlawiyya), however, is left to another article.